Characteristics of Three Different Chemiluminescence Assays for Testing for SARS-CoV-2 Antibodies. (18th January 2021) - Weber, Myriam C.; Risch, Martin; Thiel, Sarah L.; Grossmann, Kirsten; Nigg, Susanne; Wohlwend, Nadia; Lung, Thomas; Hillmann, Dorothea; Ritzler, Michael; Ferrara, Francesca; Bigler, Susanna; Egli, Konrad; et al.
Abstract : Several tests based on chemiluminescence immunoassay techniques have become available to test for SARS-CoV-2 antibodies. There is currently insufficient data on serology assay performance beyond 35 days after symptoms onset. We aimed to evaluate SARS-CoV-2 antibody tests on three widely used platforms. A chemiluminescent microparticle immunoassay (CMIA; Abbott Diagnostics, USA), a luminescence immunoassay (LIA; Diasorin, Italy), and an electrochemiluminescence immunoassay (ECLIA; Roche Diagnostics, Switzerland) were investigated. In a multigroup study, sensitivity was assessed in a group of participants with confirmed SARS-CoV-2 (n = 145 ), whereas specificity was determined in two groups of participants without evidence of COVID-19 (i.e., healthy blood donors, n = 191, and healthcare workers, n = 1002 ). Receiver operating characteristic (ROC) curves, multilevel likelihood ratios (LR), and positive (PPV) and negative (NPV) predictive values were characterized. Finally, analytical specificity was characterized in samples with evidence of the Epstein–Barr virus (EBV) (n = 9 ), cytomegalovirus (CMV) (n = 7 ), and endemic common-cold coronavirus infections (n = 12 ) taken prior to the current SARS-CoV-2 pandemic. The diagnostic accuracy was comparable in all three assays (AUC 0.98). Using the manufacturers' cut-offs, the sensitivities were 90%, 95% confidence interval [84, 94] (LIA), 93% [88, 96] (CMIA), and 96% [91, 98] (ECLIA). The specificities were 99.5% [98.9, 99.8] (CMIA), 99.7% [99.3, 99.9] (LIA), and 99.9% [99.5, 99.98] (ECLIA). The LR at half of the manufacturers' cut-offs were 60 (CMIA), 82 (LIA), and 575 (ECLIA) for positive and 0.043 (CMIA) and 0.035 (LIA, ECLIA) for negative results. ECLIA had higher PPV at low pretest probabilities than CMIA and LIA. No interference with EBV or CMV infection was observed, whereas endemic coronavirus in some cases provided signals in LIA and/or CMIA. Although the diagnostic accuracy of the three investigated assays is comparable, their performance in low-prevalence settings is different. Introducing gray zones at half of the manufacturers' cut-offs is suggested, especially for orthogonal testing approaches that use a second assay for confirmation.